Development and Testing of a Cognitive Behavioral Therapy Resource for Children's Dental Anxiety. (January 2017) - Porritt, J.; Rodd, H.; Morgan, A.; Williams, C.; Gupta, E.; Kirby, J.; Creswell, C.; Newton, T.; Stevens, K.; Baker, S.; Prasad, S.; Marshman, Z.
Cognitive Behavioral Therapy (CBT) is an evidence-based treatment for dental anxiety; however, access to therapy is limited. The current study aimed to develop a self-help CBT resource for reducing dental anxiety in children, and to assess the feasibility of conducting a trial to evaluate the treatment efficacy and cost-effectiveness of such an intervention. A mixed methods design was employed. Within phase 1, a qualitative "person-based" approach informed the development of the self-help CBT resource. This also employed guidelines for the development and evaluation of complex interventions. Within phase 2, children, aged between 9 and 16 y, who had elevated self-reported dental anxiety and were attending a community dental service or dental hospital, were invited to use the CBT resource. Children completed questionnaires, which assessed their dental anxiety and health-related quality of life (HRQoL) prior to and following their use of the resource. Recruitment and completion rates were recorded. Acceptability of the CBT resource was explored using interviews and focus groups with children, parents/carers and dental professionals. For this analysis, the authors adhered to the Mixed Methods Appraisal Tool criteria. There were 24 families and 25 dental professionals participating in the development and qualitative evaluation of the CBT resource for children with dental anxiety. A total of 56 children agreed to trial the CBT resource (66% response rate) and 48 of these children completed the study (86% completion rate). There was a significant reduction in dental anxiety (mean score difference = 7.7, t = 7.9, df = 45, P < 0.001, Cohen's d ES = 1.2) and an increase in HRQoL following the use of the CBT resource (mean score difference = -0.03, t = 2.14, df = 46, P < 0.05, Cohen's d ES = 0.3). The self-help approach had high levels of acceptability to stakeholders. These findings provide preliminary evidence for the effectiveness and acceptability of the resource in reducing dental anxiety in children and support the further evaluation of this approach in a randomized control trial. Knowledge Transfer Statement: This study details the development of a guided self-help Cognitive Behavioral Therapy resource for the management of dental anxiety in children and provides preliminary evidence for the feasibility and acceptability of this approach with children aged between 9 and 16 y. The results of this study will inform the design of a definitive trial to examine the treatment- and cost-effectiveness of the resource for reducing dental anxiety in children.